Lived experience, power that a degree cannot give you: a phenomenological study of one Hispanic woman leader in academia - Perez, Mayra; Kelley, Allyson; Ceballos, Venice; Milligan, Kelley; Cabrera, Alejandra (Frontiers in Education, 2024)
Introduction Structural racism, bias, and discrimination within institutions of higher education prevent Hispanic women from becoming university leaders and professors, especially when they do not have a formal degree. Hispanic leaders in higher education often have lived experiences based on their cultural values, family connections, and time working in community settings. However, lived experience is not always viewed as an equal qualification to college degrees when it comes to teaching, leading, or managing programs and departments. Methods The purpose of this study is to present a case study of one program operations director (leader) working at a University who does not have a terminal or advanced degree but holds the lived and professional experiences of working in community health worker programs with minority and underserved populations. This study examined her experience as a Hispanic female leading in higher education. We used qualitative phenomenological methods grounded in a descriptive case study design to inform our work. Results The themes from the analysis process represent how LE influences the participant’s work as a leader in academia and give insight into how she navigates academia without a college degree. Discussion Higher education must meet the needs of Hispanic students and leaders. By elevating Hispanic women in leadership positions, even without degrees, institutions of higher education are demonstrating a commitment to Hispanic student support, development, diversity, and culture.